Thomas Ball Barratt and 'the Spirit of Unity'. Issue 1 (April 2015) - Hegertun, Terje
Abstract : This paper describes the life of one of the most important early European Pentecostals, T. B. Barratt, and shows how his vision for the purpose of Pentecostalism changed over time from one that saw it as a renewal or restorationist movement, to a second phase when he accepted the need to establish specifically Pentecostal denominations — or to become more partisan, and to his final phase when he emphasized that 'Pentecost is for all'. The Norwegian setting for Barratt's work and quotations from his Norwegian writings are used to support the argument.